A gentleman detective and other western stories [large type] - Prosch, Richard (Thorndike Press large print softcover western, 2023)
"Con Men and Carved Birds! Lawmen and artists! Aebelskivers and cabbage. Spur-Award winner Richard Prosch has roped together an exciting new collection of stories with themes as vast as the wide open frontier and as close as the human heart. Waking Face - A sleepless man is tortured by the lost face of his wife's killer-a visage he can't remember, but at the same time, will never forget. Hard Times for the Vanilla Cream Kid - a would-be bank robber invents the perfect heist, but does he have the stomach for it? The Magic of Summerland - Nine year-old enemies of a long gone war forge a culinary feast in Nebraska hill country. The Testament of Eve - A girl comes to grips with her strange affinity for snakes and a heinous crime couched in shadows. The Gentleman Detective - A boarding house guest deciphers a robbery from the perspective of past experience. Fifteen explorations in short western fiction carry readers to the edge of the literary frontier and beyond, charting new trails in suspense, romance, and adventure"--